STUDI FENOMENOLOGI PENGALAMAN PASIEN DENGAN TB YANG TERINFEKSI COVID-19 SELAMA PANDEMIDI RSUP DR. M.DJAMIL PADANG - Titis Anggleni; Rhadiatul Aulia Sari Junaidi (CV. Adiba Aisha Amira, 2024)
Tuberculosis is still a health problem in Indonesia today. At the same time, Indonesia is also facing a corona virus outbreak and TB patients must be more vigilant. The stigma of Tuberculosis causes mental trauma, suffering, late diagnosis and non-compliance with therapy. The lockdown imposed due to Covid -19 exacerbated the fears of each patient. The aim of this study was to explore the experiences of patients with TB infected with Coivd 19 during the pandemic in the pulmonary ward of RSUP Dr. M. Djamil Padang. This research uses a qualitative method with a phenomenological approach. four participants were selected using purposive sampling techniques and data was collected through in-depth interviews. The results of the interviews were transcribed verbatim and analyzed using the Collaizi method. The research results showed 3 themes, namely